Screen Printed Gold Electrode with Cysteamine and Single Walled Carbon Nanotubes for the Recognition of Prostate Specific Antigen. (2018) - Pandey, Padmaker; Pandey, Anamika; Shukla, Nikhil.K.
Abstract: During the development of highly sensitive and stable immunosensors, it is requisite to create new types of electrodes that allow for fast and simple measurements of specific biological interactions. In the present study, gold screen printed electrode platform was modified and functionalized by Self Assembled Monolayer (SAM) and Single walled Carbon nanotubes (SWNTs) is done for the immunosensing of Prostate Specific Antigen (PSA). On the modified electrode, monoclonal Antibody (mAb) of PSA were immobilized which reacts with PSA antigen in the sample and corresponding current signals were measured by Differential Pulse voltammetry (DPV) and Electrochemical Impedance Spectroscopy (EIS) with the help of electrochemical work station.